THE SIMPLEX - PREEMPTIVE GOAL PROGRAMMING WITH BRANCH AND BOUND METHOD FOR OPTIMIZING WASTE VEHICLE ROUTES AND TRANSPORTATION - Fadhila, Rifa; Rarasati, Niken; Rozi, Syamsyida; Putra, Fernando Mersa (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
This research discusses the optimization of the assignment of waste vehicle routes and transportation, which are responsible for transporting waste from temporary disposal sites to final disposal sites. The aim is to minimize the remaining waste at temporary disposal sites, thus creating a clean and comfortable environment. The focus of this research is determining the number of trips (rit) for each vehicle (dump trucks and arm roll trucks) on each route. Besides aiming to minimize the remaining waste at temporary disposal sites as the main priority, there are also other priorities, namely minimizing fuel usage and the working time within a day. Therefore, in accordance with the characteristics of the problem, where there are multiple objectives and an integer solution is required, The Simplex-Preemptive Goal Programming with the Branch and Bound method is proposed as the solution method. The optimal solution has been obtained. The result includes the optimal number of trips (rit) for each waste transport vehicles (dump trucks and arm roll trucks) on each routes.